Late Prevertebral and Spinal Abscess following Chemoradiation for Laryngeal Squamous Cell Carcinoma - Jawad Hindy; Ilan Shelef; Yuval Slovik; Ben-Zion Joshua (Case Reports in Otolaryngology)
Objective. Advanced primary supraglottic tumors (i.e., T3 or T4) have traditionally been treated surgically and postoperative radiotherapy. In the last 2 decades, some patients were treated with chemoradiation avoiding surgery. Case Report. We describe a 55-year old female who presented with respiratory distress and paraplegia seven years after treatment for a T3N0M0 supraglottic squamous cell carcinoma. CT scan showed prevertebral and intraspinal air descending from C4 to D3 vertebras. Epidural and prevertebral abscesses were confirmed by neck exploration. Necrosis was observed in the retropharyngeal, prevertebral, and vertebral tissues. Conclusion. Prevertebral and spinal abscess may result from chemotherapy and radiotherapy to the head and neck. Physicians caring for head and neck cancer patients treated with chemotherapy and radiation should be aware of this rare severe complication.